Concordance between HER‐2 status determined by qPCR in Fine Needle Aspiration Cytology (FNAC) samples compared with IHC and FISH in Core Needle Biopsy (CNB) or surgical specimens in breast cancer patients. Issue 9 (5th August 2016) - Rodriguez, Claudia; Suciu, Voichita; Poterie, Audrey; Lacroix, Ludovic; Miran, Isabelle; Boichard, Amélie; Delaloge, Suzette; Deneuve, Jacqueline; Azoulay, Sandy; Mathieu, Marie-Christine; Valent, Alexander; Michiels, Stefan; et al.
Abstract : Determining the status of HER2‐neu amplification and overexpression in breast cancer is crucial for prognosis but mostly for treatment purposes. Standard techniques include the determination of IHC in combination with in situ hybridization techniques to confirm a HER2‐neu amplification in case of IHC2+ using either a core‐needle biopsy or a surgical specimen. qPCR has been also demonstrated to be able to determine HER2 status, mostly in core biopsies or in surgical specimens. Fine‐needle aspiration is a reliable, quicker and less invasive technique that is widely used for diagnosis of invasive breast cancer. In this study, we assessed the performance of qPCR in invasive breast carcinomas to determine HER2‐neu status by using fine‐needle aspiration samples and comparing to standard IHC and FISH. From a total of 154 samples from patients who had nodular breast lesions and attended the 1‐day‐stop clinic at the Gustave Roussy from March 2013 to October 2014, qPCR was able to determine the HER2 status in a mean of 3.7 days (SD 3.1). The overall concordance with standard HER2‐testing was very high: 97% (95% CI 0.94 to 0.99); sensitivity was 96% (0.87–1), specificity 98% (0.95–1) and positive and negative predictive values 88% (0.75–1) and 99% (0.98–1), respectively. In conclusion, our study demonstrates that qPCR performed using fine‐needle aspiration samples from a primary tumour is a reliable and fast method to determine HER2/neu status in patients with early breast cancer. Highlights: HER2 status is crucial in early breast cancer for prognostic and treatment purposes. Standard IHC and FISH testing require large samples and might be costly and lengthy. FNAC is a reliable method for diagnosis of invasive breast carcinoma. qRT‐PCR allows for HER2 status determination in FNAC with high concordance rates.